the “Pohutu Momulanga”: Penganugerahan Gelar Adat dalam Budaya Gorontalo untuk Membangun Sistem Tata Kelola Pemerintahan - Lisdawati Muda (Al-Ulum, 2021)
This article focuses on the study of Pohutu Momulanga values as the Gorontalo local wisdom in building good governance system. Good governance system requires a leader who has good characters, therefore it is interesting to examine the local wisdom values in relation to build a good leader in government. To explore the Pohutu Momulanga values and the leader work performance, this study uses library research. Data was collected through the book about Pohutu Momulanga traditional ceremony, the autobiography of the regent of Boalemo Regency in Gorontalo province and supported by interview. Data analysis used triangulation techniques that matched the data in the literature and the results of interviews. The study showed that the Regent of Boalemo Regency in Gorontalo Province awarded the customary title, because he has the values of Pohutu Momulanga in his work performance, namely very religious, high-minded, self-dicipline, insight, enamoured, and brave.